The Middle East in international relations : power, politics and ideology - Halliday, Fred (Contemporary Middle East, 2005)
Fred Halliday is one of the most authoritative scholars writing on the Middle East today. His book has been composed as an introduction to the subject for students, and those new to the field, with the objective of setting the Middle East within the broader context of contemporary international relations.